Case series study of nosocomial Legionnaires’ disease in Apulia region (southern Italy): The role of different molecular methods in identifying the infection source: Infection source in nosocomial Legionnaires' disease - De Giglio, Osvalda; D'Ambrosio, Marilena; Calia, Carla; Spagnuolo, Valentina; Oliva, Marta; Lopuzzo, Marco; Apollonio, Francesca; Triggiano, Francesco; Diella, Giusy; Scaturro, Maria; Ricci, Maria Luisa; Caringella, Maria Elena; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Legionnaires’ disease is a severe form of pneumonia caused by the inhalation or aspiration of water droplets contaminated with Legionella pneumophila and other Legionella species. These bacteria are commonly found in natural habitats and man-made water systems. Legionnaires’ disease is a significant public health problem, especially in healthcare settings where patients may be exposed to contaminated environmental sources. Nosocomial outbreaks have been reported worldwide, leading to high morbidity and mortality rates, and increased healthcare costs. This study aimed to compare, the clonal relationship of clinical L. pneumophila strains from two different hospitals with L. pneumophila strains isolated from the water supply.Methods: In the period from 2019 to 2021, clinical and environmental strains involved in three cases of legionellosis were compared by means of pulsed field gel electrophoresis and sequence based typing techniques.Results: Our findings highlight the persistence of clonally distinct strains within each hospital examined. Furthermore, the L. pneumophila strains detected from hospital environmental sources were related to the clinical strains isolated, demonstrating the nosocomial origin of these cases.Conclusions: Therefore, it is important to implement more accurate surveillance systems both for epidemiological studies and to check the effectiveness of remediation procedures. (www.actabiomedica.it)